SURG-19. REORGANIZATION OF LANGUAGE ENABLES SAFE RESECTION OF TUMORS IN AND AROUND BROCA'S AREA. (11th November 2019) - Holmes, Emma; Kerr, Keith; Kadipasaoglu, Cihan; Tandon, Nitin
Abstract: INTRODUCTION: Since its discovery in the 1800s, Broca's area has been viewed as a critical node for language production. Previously, pathologies in this area have been considered unresectable due to concern for producing iatrogenic language production deficits. Emerging literature suggests that although acute lesions in this area can cause widespread deficits, slow growing lesions are less correlated with these deficits due to cortical language reorganization. Based on this data, we managed a cohort with Broca's area lesions with surgical resection using awake intra-operative language mapping. METHODS: All 150 awake craniotomies performed by the senior author over a twelve-year period (2006–2017) at a single institution were reviewed. For each patient the imaging was carefully evaluated to localize the neoplasm relative to pars triangularis or pars opercularis in the language dominant hemisphere. Language dominance was confirmed using WADA testing or fMRI. All patients underwent cortical language mapping using a battery of tasks coupled with cortical stimulation. RESULTS: A total of 31 surgeries in 29 patients (65.5% male, 86.2% righthanded) were identified. The average age was 41. Patients presented with seizures (64.5%), speech difficulties (35.5%) or headaches (19.4%). A gross or near total resection was achieved in 26/29 (89.7%) of patients. Pathological evaluation revealed grade 2 gliomas (8), grade 3 gliomas (13) and glioblastoma (9). Post-operatively, 8 (25.8%) patients had new or worsening speech deficits, all of which resolved to baseline at follow-up. CONCLUSION: Broca's area lesions can be safely resected in patients using an awake craniotomy technique with language mapping. In our series, the majority of patients had gross or near total resections, few patients had new deficits, and none had permanent new deficits. Considering the increasing evidence in favor of cytoreduction to manage glial neoplasms, this technique should be employed routinely for pathologies in this area to optimize patient outcomes.